Aktivitas Antibakteri Ekstrak Etanol Daun Ketepeng Cina (Cassia alata L.) Terhadap Beberapa Bakteri Penyebab Infeksi Kulit - Ika Reski Fitriani; Fitriana Fitriana; Siska Nuryanti (Makassar Natural Product Journal (MNPJ), 2023)
Skin infections are one of the health problems that often occur in tropical countries which can be caused by several microorganisms such as bacteria, parasites, viruses, and fungi. One of the plants that can be used to treat skin infections caused by bacteria is the Chinese ketepeng leaf (Cassia alata L.), which contains antibacterial compounds. The purpose of this study was to determine the antibacterial activity of the ethanolic extract of the leaves of Chinese ketepeng (Cassia alata L.) against several bacteria that cause skin infections. Chinese ketepeng leaf simplicia was extracted by maceration method and then evaporated to obtain a thick extract. Then an antibacterial screening test was carried out, testing the value of the Minimum Inhibitory Concentration (MIC), Minimum Kill Concentration (KBM) with variations in the concentration of each test of 0.5%, 0.1%, 0.2%, 0.4%, 0, 8%, 1.6%, 3.2%, 6.4%, and 12.8%, and the antibacterial activity test with varying concentrations of 5%, 10%, and 20% against several bacteria, namely Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Propionibacterium acnes. Based on the results, the MIC values ​​for Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa were 1.6%, and Propionibacterium acnes was 0.4%. The MBC value for Staphylococcus aureus, Staphylococcus epidermidis, Propionibacterium acnes is 3.2%, and Pseudomonas aeruginosa is 6.4%. And the antibacterial activity test obtained the largest diameter of the inhibition zone at the optimum concentration of 20% on the test bacteria. Based on this research, the ethanolic extract of the leaves of the Chinese ketepeng (Cassia alata L.) has potential as an antibacterial.